The Propensity to Consume: Reply - Gilboy, Elizabeth W. (Quarterly Journal of Economics, 1939)
Journal Article The Propensity to Consume: Reply Get access Elizabeth W. Gilboy Elizabeth W. Gilboy Harvard University Committee on Research in the Social Sciences Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 53, Issue 4, August 1939, Pages 633–638, https://doi.org/10.2307/1883285 Published: 01 August 1939